1996
DOI: 10.1212/wnl.47.2.552
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous multivessel cervical artery dissection in a patient with a substitution of alanine for glycine (G13A) in the alpha 1(I) chain of type I collagen

Abstract: Cervical artery dissection occurs spontaneously and in multiple vessels with surprising frequency. An underlying arteriopathy is frequently suspected, but specific causes of vascular fragility are rarely identified. We describe a 35-year-old woman who developed multiple cervical artery dissections after scuba diving. She had no stigmata of connective tissue disease apart from bluish sclerae, and no family history of arterial dissection or congenital musculoskeletal disease. Analysis of the COL1A1 gene that enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 14 publications
2
46
0
1
Order By: Relevance
“…We furthermore analyzed the sequences of exons 4 to 10 of COL1A1, because in a singular CAD patient with minor signs of OI, a mutation had been found in exon 6. 29 A COL3A1 missense mutation was detected in both affected patients from family 1, as well as in the 2 patients' mothers (who are sisters). Clinical signs of connective tissue weakness were absent and skin biopsy findings were normal.…”
Section: Martin Et Al Familial Cervical Artery Dissections 2927mentioning
confidence: 96%
“…We furthermore analyzed the sequences of exons 4 to 10 of COL1A1, because in a singular CAD patient with minor signs of OI, a mutation had been found in exon 6. 29 A COL3A1 missense mutation was detected in both affected patients from family 1, as well as in the 2 patients' mothers (who are sisters). Clinical signs of connective tissue weakness were absent and skin biopsy findings were normal.…”
Section: Martin Et Al Familial Cervical Artery Dissections 2927mentioning
confidence: 96%
“…However, patients occasionally develop dissection of the aorta 16 and other large vessels. 17 Although a targeted disruption of the Col1a1 gene has not been performed, the random insertion of the Molony murine leukemia virus into the first intron of Col1a1 inactivated the gene in most tissues, including blood vessels. 18,19 These mice die at day 11 to 14 of embryonic age from rupture of blood vessels.…”
mentioning
confidence: 99%
“…15 However, all have typical findings of the skin and the body structure and could be ruled out in the present case because of the patient's history and physical examination. Mayer et al reported one case of spontaneous multivessel cervical artery dissection in a patient who had a mutation in the type I collagen gene and no family history of arterial dissection, 16 and that case can be considered as a mild phenotypic variant of osteogenesis imperfecta, which should be also included in the differential diagnosis of the present case. Another possible diagnosis is eosinophilic arteritis, which is also complicated by multiple arterial dissections, 17 but is unlikely in the present case because the signs and symptoms of chronic systemic inflammatory disease were absent before the onset of renal infarction, and because eosinophilia did not occur during the clinical course.…”
Section: Discussionmentioning
confidence: 78%